Peran Lingkungan Keluarga Terhadap Perkembangan Mental Anak: Tinjauan Psikologi Islam - sitirodiyahawaliyah siti; taufik rahman (Psychospiritual: Journal of Trends in Islamic Psychological Research, 2025)
This study explores the influence of the family environment on children's mental development within the framework of Islamic psychology. A qualitative approach using the literature review method was employed to gather data from various relevant sources, including Islamic references and psychological studies. The findings indicate that the family environment plays a central role in shaping a child's mental well-being emotionally, morally, and spiritually. Parent-child interactions, patterns of communication, and the values instilled from an early age have been shown to significantly impact development. From the perspective of Islamic psychology, the family is not only a place of refuge but also the first environment where children are introduced to the values of tawhid (monotheism), ethics, and exemplary conduct. In conclusion, the more harmonious and Islamic the family environment is, the greater its contribution to the mental stability and growth of the child. This study emphasizes the importance of building a family that is not only socially functional but also spiritually strong, so that children may grow with a healthy and balanced personality.